Fundamental concepts in engineering mechanics - Chakraborty, Suman (Everest Publishing House, 2002)
Fundamental concepts in engineering mechanics / Chakraborty, Suman. -- Kolkata: Everest Publishing House, 2002 620.1 C426 No. of Copies : 1